APLIKASI “BATANG CERDAS DIGITAL” SEBAGAI SOLUSI INTERVENSI EDUKATIF DAN KOLABORATIF DALAM PENGASUHAN ANAK DI ERA TEKNOLOGI DIGITAL - Nabilah, Igriya Fauzi (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2025)
The excessive use of digital devices among children has triggered various psychosocial problems, ranging from digital addiction to behavioral deviations such as exposure to inappropriate content. The lack of digital literacy among parents and teachers exacerbates this situation, thereby requiring a contextualized innovation to address these challenges. This study aims to develop Batang Cerdas Digital, a digital literacy companion platform designed for parents and teachers to monitor and guide children's use of gadgets. The research applies a modified Research and Development (R&D) approach based on Borg and Gall’s model, focusing on five stages: needs analysis, initial product design, expert validation, product revision, and early dissemination. Data were collected through field observations, informal interviews, and community service activities involving parents and teachers in Batang Regency. The result of this study is a web-based application prototype featuring eight core functions, including screen time monitoring, content filtering, break reminders, digital agreement tools, and online consultations with professionals. This innovation is considered theoretically and practically effective, as it is developed based on real community needs, user participation, and supported by recent scholarly literature on digital literacy and child development. The application is expected to serve as a model for digital intervention to prevent behavioral disorders among children due to uncontrolled technology use. Keywords: Educational Innovation, Digital Literacy, Digital Parenting